Baseline-free Damage Imaging Algorithm using Spatial Frequency Domain Virtual Time Reversal - Castro, Bruno Albuquerque; Baptista, Fabricio Guimaraes; Ardila, Jorge Alfredo; Ciampa, Francesco (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Structural health monitoring techniques are widely used in industry applications to guarantee the integrity of several types of components. This article proposes a baseline-free damage imaging algorithm based on Spatial Frequency Domain Virtual Time Reversal (SFD-VTR). Virtual time reversal (VTR) is an alternative to traditional time reversal as it reduces the burden of physically back-propagating re-emitted signals by applying signal operations between the transmitted and received waveforms. However, VTR rely on the reconstruction of the emitted signal in the time domain, which involves significant data manipulation causing sampling errors of reconstructed signals. Novel SFD-VTR damage indices were here proposed to enhance defect detection as they do not require the time domain reconstruction of re-emitted signals. Experimental results showed that the proposed algorithm was able to localise material flaws and can be use as Human Machine Interface (HMI).
Keywords: Aluminum; baseline-free; damage imaging; guided waves; Image reconstruction; Imaging; Imaging Algorithm; Informatics; Mathematical models; signal processing; Time-domain analysis; Ultrasound; Video recording; virtual time reversal